PELATIHAN PROGRAM MISCROSOFT POWER POINT UPTD SD NEGERI KUNATENA DI DESA KOLANA SELATAN - Lakafing, Seprianus; Abuikari, Seraya; Malmau, Shalina Sella; Lelangulu, Sherly Yoane; Tande, Simon; Klakik, Lasarus; Kelendonu, Julio; Molina, Jon Idrison (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In today's digital era, computer-based information and communication technology has influenced various aspects of life including education, it is undeniable. Tribuana Kalabahi University, Faculty of Mathematics and Natural Sciences, Informatics Engineering Study Program Class B, Semester V carried out a Microsoft Power Point training service activity in East Alor District, South Kolana Village, Dusun II Kunatena, an activity that aims to facilitate students in making presentation media that is useful for facilitate learning process with a face-to-face method where students meet directly with students to conduct training, and Q&A. Training participants are divided into groups, each group is accompanied by several students. To determine the success of the program activities that have been implemented, an evaluation is carried out. The evaluation is carried out by giving a small test to determine the level of understanding of students regarding the power point material. The conclusion of this activity is that the service has succeeded in increasing students' knowledge in applying Microsoft Power Point. Students at Kunatena Elementary School feel helped by the training that has been carried out so that they can use laptops. Students gave a very positive response to the activities carried out and considered these activities very useful.